The Treatment With the SGLT2 Inhibitor Empagliflozin Modifies the Hepatic Metabolome of Male Zucker Diabetic Fatty Rats Towards a Protective Profile - Aragón-Herrera, Alana; Otero-Santiago, Manuel; Anido-Varela, Laura; Moraña-Fernández, Sandra; Campos-Toimil, Manuel; García-Caballero, Tomás; Barral, Luis; Tarazón, Estefanía; Roselló-Lletí, Esther; Portolés, Manuel; Gualillo, Oreste; Moscoso, Isabel; et al. (Frontiers in Pharmacology, 2022)
The EMPA-REG OUTCOME (Empagliflozin, Cardiovascular Outcome Event Trial in patients with Type 2 Diabetes Mellitus (T2DM)) trial made evident the potentiality of pharmacological sodium-glucose cotransporter 2 (SGLT2) inhibition for treating patients with diabetes and cardiovascular disease. Recent evidences have shown the benefits of the SGLT2 inhibitor empagliflozin on improving liver steatosis and measures of liver fibrosis in T2DM patients. Metabolomic studies have been shown to be very useful to improve the understanding of liver pathophysiology during the development and progression of metabolic hepatic diseases, and since the effect of empagliflozin or other SGLT2 inhibitors on the whole metabolic profile of the liver has never been analysed before, we decided to study the effect of the treatment with empagliflozin for six weeks on the liver of male Zucker diabetic fatty (ZDF) rats using an untargeted metabolomics approach, with the purpose to contribute to elucidate the benefits at hepatic level of the use of empagliflozin. We found that empagliflozin is able to change the hepatic lipidome towards a protective profile, through an increase of monounsaturated and polyunsaturated glycerides, phosphatidylcholines, phosphatidylethanolamines, lysophosphatidylinositols and lysophosphatidylcholines. Empagliflozin also induces a decrease in the levels of the pro-inflammatory markers IL-6, chemerin, and chemerin receptor in the liver. Our results provide new evidences regarding the molecular pathways through which empagliflozin could exert hepatoprotector beneficial effects in T2DM.